THE INFLUENCE OF PERSONAL FINANCIAL MANAGEMENT, FINANCIAL LITERACY, AND RISK PERCEPTION ON BITCOIN INVESTMENT DECISIONS AMONG GENERATION Z IN MALANG CITY, INDONESIA - Lindananty Lindananty; George Michael Hermanto Lioe (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study analyzes the effects of personal financial management, financial literacy, fundamental analysis, technical analysis, and risk perception on Bitcoin investment decisions among Generation Z in Malang. Using data from 100 respondents and applying PLS-SEM, the results show that only technical analysis has a significant positive influence on investment decisions. The other variables—personal financial management, financial literacy, fundamental analysis, and risk perception—do not show significant effects. The model demonstrates strong explanatory power with an R² of 0.979, indicating that these factors collectively explain most of the variation in Bitcoin investment decisions.